The relationship among body image, psychological distress, and quality of life in young breast cancer patients: a cross-sectional study - Yao, Hongmei; Xiong, Meidi; Cheng, Yuping; Zhang, Qingyuan; Luo, Ying; Ding, Xiegang; Zhang, Chunhua (Frontiers in Psychology, 2024)
The aim of this study is to explore the interrelationships among body image perception, levels of psychological distress, and the quality of life (QOL) experienced by youngbreast cancer patients Methods:This study analyzed data from 339 young femalebreast cancerpatientsaged between 18 and 40 years ( mean age was 33.47 years)from August 2023 to February 2024. Data on demographic characteristics, psychological distress, body image, medical coping, and QOL of youngbreast cancer patientswere collected. Psychological distress, body image, medical coping, and QOL were measured using the Distress Thermometer (DT), Hospital Anxiety and Depression Scale (HADS), Body Image Scale (BIS), Medical Coping Modes Questionnaire (MCMQ), and Functional Assessment of Cancer Therapy-Breast (FACT-B), respectively. Multiple regression analysis was conducted to examine factors influencing QOL. Results:After adjusting for covariates, significant predictors of QOL in young survivors included psychological distress (β = -3.125; p = 0.002), anxiety and depression (β = -4.31; p < 0.001), cognitive dimension of body image (β = -0.218; p = 0.027), behavioral dimension of body image (β = 0.579; p = 0.047), and confrontational dimension of medical coping (β = -0.124; p = 0.01).The findings suggest that higher levels of body image concerns and psychological distress are associated with poorer QOL among young female breast cancerpatients. Furthermore,breast cancer patientsfacing with more positive medical coping strategies predicted a higher QOL.